Availability and Access to Medications for Puberty Induction and Maintenance in Adolescents with Hypogonadism in the Arab Region. (20th July 2022) - Deeb, A.; AlSaffar, H.; Hamza, R. T.; Abass, M.; Habeb, A. M.
Abstract : Background . Inducing puberty in hypogonadal patients enables achieving normal final adult height and healthy bone mass accrual and improves fertility potential. Reliable availability and access to medicines remain a challenge around the world, particularly in low-income countries. Aim . We aimed to describe the availability/access to medications used for inducing and maintaining puberty in centers within the Arab region. Method . A cross-sectional survey was conducted using a link to an online questionnaire, which was emailed to paediatric endocrinologists in the Arab region. The questionnaire consisted of three questions related to the availability of various forms of sex hormones. Results . 99 physicians from 16 countries participated in the study. The commonest available form of estrogen was conjugated estrogen (29% of centers), followed by ethinylestradiol (26%). Depot estradiol was available in 11 centers, while topical estrogen preparations of gel and patches were available in 6 and 10 centers, respectively. Medroxy progesterone was available in 26% of the centers, followed by norethisterone (24%). The combined forms of oral and transdermal patches of estrogen/progesterone were available in 35% and 9% of centers, respectively. Intramuscular testosterone (Sustanon) was the most commonly available preparation of testosterone, followed by the depot injection (Nebido), oral testosterone, and testosterone gel and cream. Conclusions . We report the first available data on medications used for puberty induction and maintenance in paediatric hypogonadism in the Arab region. Recommended preparations for this purpose are not widely available. Creating an essential list of medications used in paediatric endocrinology disorders might improve availability, access, and consequently practice.